Identification of dangerous preservative content in shrimp paste (acetes sp.) circulating in the traditional markets of Sumbawa City - Dinda Sari; Chairul Anam Afgani (Journal of Agritechnology and Food Processing, 2024)
Shrimp paste is a processed food product produced by fermenting shrimp or fish through the addition of salt or other permitted ingredients. This research was conducted to determine whether or not there were dangerous preservatives formaldehyde and borax in shrimp paste circulating in the traditional markets of Sumbawa City. This type of research is laboratory-based qualitative and quantitative descriptive using a Completely Randomized Design (CRD). The samples used were 4 solid block dried shrimp paste samples obtained from the Labuan market, Brang seed market, Seketeng market and downstream Moyo market. The test parameters carried out were formalin test, borax test, physical color test, hedonic organoleptic quality test and water content value test. Based on the identification results, the shrimp paste samples that tested negative contained the dangerous preservatives formaldehyde and borax because they did not show any color change. The physical color test results showed that the ◦Hue ranged between 68.11-71.09, which indicated that the shrimp paste was red-yellow. The results of the hedonic organoleptic quality test showed that there was no significant difference in the level of panelists' preference for the color, texture and aroma of shrimp paste. The results of the water content test yielded water content values ranging between 29%-35%. The lowest water content value was obtained in the Labuan market with a water content value of 29% and the highest water content value was in the seed brang market with a water content value of 35%. The water content of shrimp paste circulating in the traditional markets of Sumbawa City is in accordance with the standards set by SNI 2716:2016 concerning the water content of dry solid block shrimp paste, namely a maximum of 35%.